2018
DOI: 10.3389/fams.2018.00056
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Social Networking Site Usage and Participation in Protest Activities

Abstract: A methodological approach is developed for exploring the relationship between the use of social networking sites and participation in protest activities. Although a recent meta-analysis study demonstrated that there is a positive association between the two, little work examining this association further appears to have been published. The methodology proposed here studies the patterns of the relationship between nine social media and five types of protest activity using the techniques of multiple corresponden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…This process, like every (especially large-scale and effective) phenomenon, can be considered from the point of view of a constructive and destructive impact on the social environment. Destructiveness is determined by the following characteristics of the digital political context, functioning online (Ilie, 2004;Masías et al, 2018;Volkova & Panchenko, 2016):…”
Section: Introductionmentioning
confidence: 99%
“…This process, like every (especially large-scale and effective) phenomenon, can be considered from the point of view of a constructive and destructive impact on the social environment. Destructiveness is determined by the following characteristics of the digital political context, functioning online (Ilie, 2004;Masías et al, 2018;Volkova & Panchenko, 2016):…”
Section: Introductionmentioning
confidence: 99%
“…online discourse fields various in scale, has increased. Therefore, there increased their ability to generate triggers whose consumption can affect users' decisions and induce the sociopolitical action in the offline space (Masías, Hecking, & Hoppe, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this development, researchers have begun to investigate the role of new media channels for purposes of nature conservation. Inspired by studies from the political sciences that have demonstrated how social media usage may contribute to political activism (Boulianne, 2015; Masías et al, 2018), several researchers proposed social media as a tool for education about and participation in environmental issues (Pearson et al, 2016). To investigate the possibilities of environmental social media usage, several studies have utilized existing social networking data to investigate content, places, or agents of environmental posts (Di Minin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%